Itinerâncias e permanências: a representatividade e os desafios dos ciganos no Rio Grande do Sul (2006-2025) - Silva, Patrick de Carvalho da (2025)
This dissertation aims to analyze the Roma communities of Rio Grande do Sul, observing their itinerancy, permanence, and the current context of their struggles and social achievements between 2006 and 2025. Roma are one of the Traditional Communities that inhabit various regions of Brazil. Their histories date back to the period of what was then Portuguese America, when the first Roma were sent as exiles from Portugal. Among the diverse ethnicities that comprise these groups and are present in Brazil, we can highlight the Calon, Rom, and Sinti Roma. Whether as itinerant, semi-nomadic, or settled Roma, most of them have deep connections with their cultures and traditions, in contrast to the stereotypes and prejudices that exclude and marginalize them. Over the past 19 years, Roma have achieved representation and some public policies through social awareness movements and dialogues with non-Roma. Although many Roma leaders have acted as protagonists in various regions of the country, working alongside government agencies in the pursuit of social and economic inclusion for Roma, there are still many barriers to overcome. Roma have an agraphic history, where writing gives way to the oral tradition of their stories. Beyond a cultural aspect, oral tradition is integral to Roma identity. The lack of historiographical materials, the limited contact between Roma and non-Roma, and itinerancy are just some of the challenges facing this research proposal. In contrast, many Roma and Roma leaders have supported multiethnic dialogue, aiming to broaden debates within government agencies and deconstruct the stigmas that have been built around these communities throughout history within the civil society. To learn more about the Roma of Rio Grande do Sul, we will use the descriptive process as a category of analysis, where we can observe: who these individuals are; where they came from; how they arrived in the southern region of the country and when this likely occurred; What were (or still are) the difficulties they encounter in their social relationships? How do Roma representation and identities work? We will use bibliographical sources and methodological bases, including literary works, academic papers, minutes, and periodicals produced between the 17th and early 20th centuries, which frequently featured articles on the "comings and goings" of Roma across the country. We will be able to discuss how the complex social relationships between Roma and non-Roma developed, as well as analyze the legislation and public policies that encompass these communities. We will adopt a qualitative analytical approach. In this process, we will examine the information gathered through case studies focused on interviews conducted in specific Roma camps and with the leaders and representatives of these communities. The theoretical framework for this research will address the concepts of identity, memory, representation, and thematic oral history. It is considered, in short, that although the Roma communities of Rio Grande do Sul, as in other regions of the country, still face many challenges due to marginalization, exclusion, and prejudice, broad avenues for dialogue have been opened not only with non-Roma society but also with public authorities. Public policies have also been created or redesigned to welcome and guarantee the rights of Roma people. However, some "barriers" still persist, whether in bureaucratic issues related to access to government programs or to broader dialogue with society. Roma leaders strive to ensure that the voice of Roma people is heard and their culture respected in all spaces, observing their legitimacy as citizens.